A dissimilar biosimilar? Lichenoid drug eruption induced by an infliximab biosimilar. (7th February 2018) - Gonzalez, N.; Patel, P.; Han, G.
Summary: The advent of therapeutic antibodies, or biological medications, has transformed the treatment of many inflammatory diseases in dermatology. Recently, the development of biosimilars, biological drugs that are highly similar in quality, safety and efficacy to approved biologics, has changed this landscape. Although biosimilars are not identical to their reference product, they are required to have the same mechanism of action, route of administration, dosage form and strength as the reference product. This also leads to the possibility that subtle differences in the activity of these biosimilars can lead to differing clinical responses. We report the first case of a lichenoid eruption induced by a biosimilar to infliximab after switching from infliximab. Several days after initial infusion of the biosimilar, the patient developed a pruritic papulosquamous eruption that was biopsied to reveal a lichenoid drug eruption. Possible mechanisms for lichenoid drug eruptions as a result of tumour necrosis factor‐α inhibitor administration are discussed, along with reasons why such a reaction may occur with a biosimilar but not the original, reference product. This case report calls attention to the unique differences between biosimilars and biological medications that a clinician should consider prior to prescribing these medications. Abstract : What's already known about this topic? There have been no published case reports of lichenoid drug eruptions, or any other type of specific cutaneous drug eruption, after switching from a tumour necrosis factor‐α inhibitor biological medication to a biosimilar. What does this study add? This case report calls to attention the fact that, contrary to the relationship between oral small‐molecule drugs and their generics, significant differences can exist among biosimilars and their reference biologics, which can result in clinically relevant consequences. Linked Article:  Gonzalez et al. Br J Dermatol 2018; 178 :965–968